High-durability organic silicon conductive adhesive and preparation method thereof
By optimizing the dispersion method of conductive fillers and introducing mesoscopic phase orientation agents, nanobarrier layers and aging-resistant additives, the shortcomings of silicone conductive adhesives in terms of high temperature resistance and conductive stability are solved, and higher durability and service life are achieved.
Patent Information
- Application Number
- CN202510443359.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2025-05-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicone conductive adhesives have shortcomings in their high temperature resistance, conductive stability and long-term service performance, especially the dispersion stability and aging resistance of conductive fillers.
By optimizing the dispersion method of conductive fillers, a mesoscopic phase orientation agent is used to regulate the conductive path, and a nano barrier layer is introduced, combining aging-resistant additives and a self-healing synergistic system to improve the performance of the material in high temperature, humidity and heat and ultraviolet environments.
It realizes lower resistance drift, better mechanical stability and longer service life of conductive adhesives in high temperature environments, and is suitable for conductive packaging and bonding applications in extreme operating conditions.
Smart Images

Figure CN119955467A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a highly durable organic silicon conductive adhesive and a preparation method thereof. Background Art
[0002] Silicone conductive adhesives are widely used in aerospace, electronic packaging, automotive electronics and high-end industrial fields. Their core advantages lie in good flexibility, weather resistance and excellent electrical properties. However, existing silicone conductive adhesives still have certain technical bottlenecks in terms of high temperature resistance, conductive stability and long-term service performance.
[0003] First, there is the problem of dispersion stability of conductive fillers. Traditional silicone conductive adhesives mainly use conductive fillers such as silver powder, carbon nanotubes, and graphene, but due to the agglomeration of fillers in the matrix, the conductive path is uneven, affecting the overall conductive performance. In addition, in high temperature environments, conductive fillers are prone to oxidation or migration, resulting in conductive attenuation and accelerating material failure.
[0004] Secondly, the long-term high temperature resistance and aging resistance are insufficient. In the prior art, the high temperature resistance of most silicone conductive adhesives mainly depends on the heat resistance of the silicone matrix itself. However, in high temperature environments, problems such as mismatch in the thermal expansion coefficient of the material, accumulation of interfacial stress, and degradation of the matrix will lead to a decrease in the bonding performance of the conductive adhesive and even affect the electrical stability. In addition, factors such as ultraviolet rays, hot and humid environments, and long-term thermal oxidation aging will also reduce the service life of the conductive adhesive, making it difficult to serve for a long time under extreme working conditions. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a highly durable organic silicone conductive adhesive and a preparation method thereof to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions: The embodiment of the present invention provides a highly durable organic silicon conductive adhesive, comprising the following specific components: an organic silicon matrix, a conductive filler, a curing system, an anti-aging additive, and a tackifier; The mass fractions of each component are as follows: 50-100 parts of silicone matrix; Conductive filler 40-80 parts; Curing system 2-10 parts; 1-5 parts of anti-aging additive; 2-8 parts of tackifier; The high-durability silicone conductive adhesive also includes additives, which include a mesophase orientation agent, a self-repairing synergistic system, a nanophase interface reinforcing agent, and a nanobarrier layer; The mass fractions of each component of the additive are as follows: 2-6 parts of mesophase orientation agent; 3-8 copies of the self-repairing collaborative system; 4-10 parts of nanophase interface strengthener; Nano barrier layer 2-7 parts.
[0007] To further optimize the technical solution, the silicone matrix is any one or more of polysiloxane or modified silicone resin; the conductive filler is any one or more of silver-plated copper powder, graphene or carbon nanotubes; the curing system is any one or more of peroxide curing agent, platinum-catalyzed addition curing agent or moisture curing agent; the anti-aging additive includes any one or more of antioxidant, ultraviolet absorber and thermal stabilizer; the tackifier is any one or more of silane coupling agent or modified epoxy resin.
[0008] Further optimizing the technical solution, the mesophase orientation agent includes a block copolymer and a surface functionalized liquid crystal polymer; The block copolymer is any one or more of polyethylene oxide-polydimethylsiloxane-polyethylene oxide, polystyrene-polydimethylsiloxane-polystyrene or segmented polyurethane, and the molecular weight distribution of the block copolymer is between 10,000 and 100,000; The main chain structure of the surface functionalized liquid crystal polymer is any one or more of polystyrene, polymethyl methacrylate or polyamide, and the side chain contains any one or more of cyano, carboxyl, sulfonic acid or phosphoric acid functional groups, which are used to enhance the orientation ability of the conductive filler.
[0009] Further optimizing the technical solution, in the additive, the self-healing synergistic system includes nitrogen-doped graphene and aromatic heterocyclic functionalized silane; The nitrogen content in the nitrogen-doped graphene is 1-10 wt %, and the nitrogen exists in the form of pyridinic nitrogen, graphitic nitrogen or amine nitrogen; The aromatic heterocyclic functionalized silane contains any one or more of an imidazole ring, a thiophene ring, a benzothiazole ring or a benzimidazole ring structure, and forms a dynamic reversible hydrogen bond network with the organic silicon matrix, thereby improving the self-repairing ability of the conductive adhesive.
[0010] Further optimizing the technical solution, the nanophase interface reinforcing agent is composed of triblock nanocarbon fibers and a supramolecular network reinforcing agent; The triblock carbon nanofiber has a carbon nanofiber as the main chain and functionalized polydimethylsiloxane grafted at both ends. The diameter of the triblock carbon nanofiber is 20-200 nm and the length is 1-10 μm. The supramolecular network enhancer is composed of surface-modified Janus particles, one side of the surface of the Janus particles is modified with a hydrophobic group, and the other side is modified with a hydrophilic group, so as to improve the interface bonding force between the organic silicon matrix and the conductive filler.
[0011] Further optimizing the technical solution, the nano barrier layer is composed of a nano metal-oxide heterostructure and a conductive polymer coating; The thickness of the oxide layer on the surface of the nano-metal-oxide heterostructure is 2-20 nm; The thickness of the conductive polymer coating is 5-50 nm.
[0012] Further optimizing the technical solution, the nanometal in the nanometal-oxide heterostructure is any one or more of silver nanoparticles, copper nanoparticles or nickel nanoparticles; the oxide layer is any one or more of tin oxide, zinc oxide and aluminum oxide; the nanometal-oxide heterostructure forms a stable physical barrier on the surface of the conductive filler; The conductive polymer coating is any one or more of polypyrrole, polyaniline or polythiophene, and provides an additional electron transport channel when the conductive filler ages or partially oxidizes and fails.
[0013] A method for preparing a highly durable organic silicone conductive adhesive is prepared based on the above-mentioned highly durable organic silicone conductive adhesive, and comprises the following specific steps: S1, preparing an organic silicon matrix as a basic carrier of the conductive adhesive; S2, dispersing the conductive filler to form a stable dispersed state in the organic silicon matrix; S3, adding a curing system, the curing system is used to cross-link the silicone matrix; S4. Introduce anti-aging additives to improve the UV resistance, heat resistance and moisture resistance of the conductive adhesive; S5, adding a tackifier to enhance the interface bonding strength; S6, adding a mesophase orientation agent to optimize the conductive path of the conductive adhesive; S7, introduce a self-healing collaborative system and ensure its uniform dispersion; S8. Finally, add the nano-phase interface reinforcing agent and the nano-barrier layer, and after aging, form a stable and highly durable silicone conductive adhesive.
[0014] Further optimizing the technical solution, in step S7, when adding the self-repairing synergistic system, stirring and mixing at a speed of 500-1000 rpm for 60 minutes to ensure its uniform dispersion; Through subsequent low-temperature treatment at 40-60°C, the self-healing synergistic system forms a dynamic network, improving the fatigue resistance and self-healing properties of the conductive adhesive.
[0015] To further optimize the technical solution, in step S8, first add the nanophase interface strengthener, and use shear stirring at a speed of 3000-4000 rpm for 30 minutes to make it evenly distributed; Then, the nano-barrier layer was added under stirring conditions and continued to be stirred for 30 minutes to optimize its bonding with the silicone matrix; Finally, the conductive adhesive system is cured at a temperature of 25-40° C. for 12-24 hours to form a stable and highly durable silicone conductive adhesive.
[0016] Compared with the prior art, the present invention provides a highly durable organic silicone conductive adhesive and a preparation method thereof, which has the following beneficial effects: The highly durable silicone conductive adhesive and its preparation method optimize the dispersion mode of the conductive filler, use a mesophase orientation agent to regulate the conductive path, and introduce a nano-barrier layer to effectively reduce the oxidation and migration of the filler and improve the conductive stability. In addition, through the composite design of the anti-aging additive and the self-repairing synergistic system, the material maintains excellent bonding performance and conductivity under high temperature, humid heat and ultraviolet light environments. Compared with the prior art, the conductive adhesive of the present invention has lower resistance drift, better mechanical stability and longer service life under high temperature environments, and is suitable for conductive packaging and bonding applications under extreme working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 A schematic diagram of the composition of a highly durable organic silicone conductive adhesive proposed by the present invention; Figure 2 The present invention provides a schematic flow chart of a method for preparing a highly durable organic silicone conductive adhesive. DETAILED DESCRIPTION
[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.
[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0021] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0022] Example Reference Figure 1 This embodiment provides a highly durable silicone conductive adhesive, including the following specific components: a silicone matrix, a conductive filler, a curing system, an anti-aging additive, and a tackifier.
[0023] The mass fractions of each component are as follows: The silicone matrix is 100 parts; The conductive filler is 80 parts; The curing system is 10 parts; The anti-aging agent is 5 parts; The amount of tackifier is 8 parts.
[0024] The high-durability organic silicone conductive adhesive also includes additives, which include a mesophase orientation agent, a self-repairing synergistic system, a nanophase interface reinforcing agent, and a nanobarrier layer.
[0025] The mass fractions of each component of the additive are as follows: The mesophase orientation agent is 6 parts; The self-repair synergy system is 8 copies; The nanophase interface strengthener is 10 parts; The nano barrier layer is 7 parts.
[0026] In this embodiment, the specific components include: The organic silicon matrix is polysiloxane or modified silicone resin. In this embodiment, modified silicone resin is selected. Modified silicone resin is obtained by introducing organic functional groups (such as phenyl, vinyl, fluorine, etc.) or copolymer components into the main chain or side chain of siloxane to improve its heat resistance, adhesion, flexibility or chemical stability. The organic silicon matrix is the main component of the conductive adhesive and determines the mechanical properties, weather resistance and environmental adaptability of the conductive adhesive.
[0027] The conductive filler is silver-plated copper powder, graphene or carbon nanotubes, and graphene is selected in this embodiment. The conductive filler is a key component that determines the conductive properties of the conductive adhesive. Silver-plated copper powder can reduce the amount of silver while still maintaining good conductivity and antioxidant capacity. As a new type of carbon-based conductive filler, graphene has ultra-high conductivity and mechanical properties, and can improve the stability of the conductive network. Carbon nanotubes can form a three-dimensional conductive network, improve the conductivity of the conductive adhesive at a low filling amount, and reduce cost and density.
[0028] The curing system is a peroxide curing agent, a platinum catalyzed addition curing agent or a moisture curing agent. In this embodiment, a peroxide curing agent is selected. Peroxide curing agents such as di-tert-butyl peroxide can induce crosslinking at high temperatures to improve temperature resistance and mechanical strength. Platinum catalyzed addition curing agents such as platinum complex catalysts do not generate by-products and are suitable for high-performance electronic conductive adhesives. Moisture curing agents such as tetraethyl orthosilicate rely on moisture in the air for curing and are suitable for room temperature curing conductive adhesives.
[0029] The anti-aging additives include antioxidants, ultraviolet absorbers and heat stabilizers. In this embodiment, antioxidants are selected. Antioxidants such as hindered phenol BHT (butylated hydroxytoluene) prevent the filler and the silicone matrix from oxidative decomposition. Ultraviolet absorbers such as benzophenone UV-531 reduce the degradation of ultraviolet rays on the conductive adhesive. Heat stabilizers such as phosphates enhance the high temperature resistance of the conductive adhesive and prevent the oxidation failure of silver or copper powder.
[0030] The tackifier is a silane coupling agent (such as γ-glycidyloxypropyltrimethoxysilane) or a modified epoxy resin. In this embodiment, a silane coupling agent is selected to improve the bonding strength of the conductive adhesive and avoid peeling failure.
[0031] In this embodiment: In the additive, the mesophase orientation agent includes a block copolymer and a surface functionalized liquid crystal polymer. The additive can form a controllable mesophase orientation structure in the conductive filler, thereby optimizing the conductive path. Through the self-assembly characteristics of the block copolymer, silver powder, graphene, etc. are arranged in an orderly manner, reducing tunnel resistance and improving conductive efficiency. The liquid crystal polymer further enhances the orientation synergy at the nanoscale, making the conductive network more stable and avoiding the breakage of the conductive network due to thermal expansion or mechanical stress of the particles. The distribution of conventional conductive glue fillers is random, while this additive can make the fillers arranged in a directional manner, significantly reducing the contact resistance in the conductive path and improving conductivity.
[0032] The block copolymer is polyethylene oxide-polydimethylsiloxane-polyethylene oxide, and the molecular weight distribution of the block copolymer is between 10,000 and 100,000; The main chain structure of the surface functionalized liquid crystal polymer is polystyrene, and the side chain contains cyano, carboxyl, sulfonic acid or phosphoric acid functional groups, which are used to enhance the orientation ability of the conductive filler.
[0033] Through molecular self-assembly, a mesoscopic phase structure is formed in the dispersed phase of the conductive filler, so that the silver powder, graphene, carbon nanotubes or other conductive fillers are arranged in an orderly manner, thereby optimizing the conductive path, reducing the interface contact resistance, and improving the electrical properties and long-term stability of the conductive adhesive.
[0034] Among the additives, the self-healing synergistic system includes nitrogen-doped graphene and aromatic heterocyclic functionalized silane. This system can achieve rapid electronic compensation and mechanical repair when microcracks or tensile deformation occur in the conductive adhesive through the electron acceptor properties of nitrogen-doped graphene and the dynamic hydrogen bonding of aromatic heterocyclic rings. When the conductive network is damaged, the dynamic hydrogen bonding interaction of the imidazole ring or thiophene ring causes the conductive filler at the microcrack to re-aggregate, thereby restoring the conductive path. At the same time, nitrogen-doped graphene can stabilize the conductive network through π-π stacking and electrostatic action, prevent crack expansion, and improve durability. The nitrogen-doped structure can adjust the electron mobility, improve the conductivity, and reduce the amount of conductive filler added, reducing material costs.
[0035] The nitrogen content in nitrogen-doped graphene is 5 wt %, and the nitrogen exists in the form of pyridinic nitrogen; The aromatic heterocyclic functionalized silane contains an imidazole ring, a thiophene ring, a benzothiazole ring or a benzimidazole ring structure, and forms a dynamic reversible hydrogen bond network with the silicone matrix to improve the self-healing ability of the conductive adhesive.
[0036] The system can reorganize and repair the conductive filler through the dynamic hydrogen bonding of aromatic heterocycles when the conductive adhesive is cracked, stressed, deformed or micro-damaged, and stabilize the conductive path by the π-π stacking effect of nitrogen-doped graphene, thereby improving the long-term durability and crack resistance of the conductive adhesive.
[0037] Among the additives, the nanophase interface enhancer is composed of triblock carbon nanofibers and supramolecular network enhancers. The enhancer can optimize the bonding force between the conductive adhesive at different interfaces (such as metal-colloid, matrix-filler), prevent the conductive filler from settling and agglomerating, and enhance the bonding performance. The triblock carbon nanofibers have a flexible middle layer (PDMS) that can adaptively deform during the curing process to ensure adhesion strength and maintain good conductive network stability after high-temperature aging. The supramolecular network enhancer improves the compatibility of the silicone matrix and the filler through the interfacial amphiphilic properties of the Janus particles, thereby increasing the adhesion of the conductive adhesive on different substrates (such as metal, glass, and ceramics) by 30%-50%.
[0038] The triblock nanocarbon fiber has carbon nanofiber as the main chain and functionalized polydimethylsiloxane grafted at both ends, with a diameter of 100 nm and a length of 5 μm; The supramolecular network enhancer is composed of surface-modified Janus particles, one side of which is modified with hydrophobic groups (such as fluorocarbon chains) and the other side is modified with hydrophilic groups (such as carboxyl, amino or hydroxyl groups) to improve the interfacial bonding between the silicone matrix and the conductive filler.
[0039] The nano-phase interface reinforcing agent can optimize the dispersibility of the conductive filler in the organic silicon matrix, reduce the sedimentation and aggregation of the filler, and improve the fatigue resistance and weather resistance of the conductive adhesive.
[0040] Among the additives, the nano barrier layer is composed of a nano metal-oxide heterostructure and a conductive polymer coating. The barrier layer mainly acts on the surface of the conductive filler to prevent the oxidation failure of silver powder and copper powder, and is particularly suitable for high temperature and high humidity environments. By introducing the nano metal-oxide heterostructure, an electrochemically stable layer is formed, which can effectively block the intrusion of moisture and oxygen in a humid environment while maintaining conductivity. In addition, the conductive polymer coating (such as polypyrrole PPy) can provide additional electron transport channels. Even if part of the conductive filler fails due to aging, charge transfer can be achieved through the polymer layer, thereby extending the service life of the conductive adhesive.
[0041] The oxide layer thickness on the surface of the nano-metal-oxide heterostructure is 10 nm, which can form a stable physical barrier on the surface of the conductive filler to prevent moisture and oxygen corrosion and improve the antioxidant capacity of the conductive filler.
[0042] The thickness of the conductive polymer coating is 25 nm, which can provide additional electron transport channels when the conductive filler ages or partially oxidizes and fails, thereby maintaining the conductive properties of the conductive adhesive.
[0043] The nano-metal in the nano-metal-oxide heterostructure is silver nano-particles, copper nano-particles or nickel nano-particles; the oxide layer is tin oxide, zinc oxide or aluminum oxide.
[0044] The conductive polymer coating is polypyrrole, polyaniline or polythiophene, which provides an additional electron transport channel when the conductive filler is aged or partially oxidized and fails.
[0045] The nano-barrier layer uses nano-heterostructure to achieve dual physical and chemical protection, extending the life of the conductive filler by more than 2 times.
[0046] Reference Figure 2 The method for preparing the highly durable organic silicone conductive adhesive of this embodiment comprises the following specific steps: S1. Prepare an organic silicon matrix as a basic carrier of the conductive adhesive.
[0047] Add silicone resin to the reactor and stir at 70°C for 45 minutes to reduce its viscosity. Then, add rheology modifier under continuous stirring to form a uniform liquid matrix. To improve the flexibility and durability of the matrix, an appropriate amount of plasticizer can be added to improve the matrix's ability to encapsulate the filler.
[0048] S2. Disperse the conductive filler to form a stable dispersed state in the silicone matrix.
[0049] In the prepared silicone matrix, the conductive fillers are slowly added in sequence, and the high-speed shear stirring device is turned on at the same time, stirring at a speed of 3000 rpm for 60 minutes to ensure that the fillers are evenly distributed. To further improve the stability of the fillers, surfactants can be added to reduce the agglomeration tendency of the fillers and obtain a uniformly dispersed conductive filler system.
[0050] S3, adding a curing system, the curing system is used to cross-link the silicone matrix.
[0051] At room temperature, slowly add the curing system to the silicone matrix in which the conductive filler has been dispersed, and stir at a low speed (750 rpm) for 30 minutes to fully mix it. Add the catalyst appropriately to adjust the curing rate to avoid the problem of internal stress concentration caused by too fast curing, and form a premixed system with controllable curing.
[0052] S4. Introduce anti-aging additives to improve the conductive adhesive's resistance to UV rays, heat and moisture.
[0053] Slowly add the anti-aging additive to the controllable curing premixed system, and continue mixing at low speed (650 rpm) for 60 minutes to make it evenly dispersed. To improve the anti-aging effect, some ultraviolet light absorbers or free radical scavengers can be introduced and ultrasonic dispersion can be performed to improve the uniformity of the distribution of the additives, and the long-term stability and weather resistance of the conductive adhesive are further improved.
[0054] S5. Add a tackifier to enhance the interface bonding strength.
[0055] Under stirring conditions, slowly add the tackifier to the above-mentioned mixed system and stir for 45 minutes to ensure uniform dispersion. By controlling the molecular structure of the tackifier and optimizing its interaction with the matrix and filler, the conductive adhesive formed has better adhesion and durability in complex environments.
[0056] S6. Add a mesophase orientation agent to optimize the conductive path of the conductive adhesive.
[0057] The mesophase orientation agent was added to the uniformly dispersed conductive adhesive system, and the mixture was continuously mixed for 45 minutes using high shear stirring (2500 rpm), and the orientation of the filler was further optimized under the assistance of ultrasound. The orientation of the conductive filler was optimized, and the conductivity and durability of the conductive adhesive were improved.
[0058] S7. Introduce a self-healing collaborative system and ensure its uniform dispersion.
[0059] When adding the self-repairing synergistic system, mix it at a low speed of 750 rpm for 60 minutes to ensure that it is evenly dispersed; Through subsequent low-temperature treatment at 50°C, the self-healing synergistic system gradually forms a dynamic network, improving the fatigue resistance and self-healing properties of the conductive adhesive.
[0060] S8. Finally, add the nano-phase interface reinforcing agent and the nano-barrier layer, and after aging, form a stable and highly durable silicone conductive adhesive.
[0061] First, add the nanophase interface strengthener and use high-speed shear stirring at 3500 rpm for 30 minutes to make it evenly distributed; Then, the nano-barrier material was added under stirring conditions and continued to be stirred for 30 minutes to optimize its bonding with the silicone matrix; Finally, the conductive adhesive system was cured at a temperature of 35° C. for 18 h to form a stable and highly durable silicone conductive adhesive.
[0062] The highly durable silicone conductive adhesive prepared in the above steps was subjected to multiple tests, and the specific test contents are as follows: 1. Conductivity test Square resistance (Ωm 2 ) Test: The four-probe method is used to measure the square resistance of the conductive adhesive and evaluate its conductivity at room temperature (25°C, 50%RH).
[0063] Volume resistivity (Ω·cm) test: The volume resistivity of the material is measured by the four-probe method to examine its overall conductivity under low current.
[0064] 2. High temperature resistance test The high temperature aging test was conducted by placing the conductive adhesive in a 200°C environment for 1000 hours to test changes in its conductive properties and evaluate its stability in a high temperature environment.
[0065] 3. Bond strength test The shear strength test was used to perform tensile tests on the conductive adhesive at 25°C and 50% RH to measure its bonding strength in order to evaluate its adhesion to different substrates.
[0066] 4. Aging stability test Damp-heat aging test: Expose the conductive adhesive to an environment of 85°C and 85%RH for 1000 hours, and test its resistance change to evaluate its resistance to damp-heat aging.
[0067] The test report is shown in Table 1.
[0068] Table 1
[0069] A comprehensive evaluation was conducted on the conductivity, high temperature resistance, bonding strength and aging stability of high-durability silicone conductive adhesives. The test results showed that: 1. Excellent electrical conductivity The square resistance of this conductive adhesive is only 0.005 Ωm 2 , the volume resistivity is 1.2×10 -3 Ω·cm, which is comparable to high-end conductive adhesive products, indicating that it has excellent conductivity and is suitable for high-performance electronic packaging and connection applications.
[0070] 2.Excellent high temperature resistance After aging at 200°C for 1000 hours, the resistance change was less than 5%, indicating that the material can still maintain stable conductivity in extremely high temperature environments and can be used for high-temperature electronic component packaging and high-temperature resistant application scenarios.
[0071] 3. Good bonding strength The shear strength reaches 6.5 MPa, indicating that the conductive adhesive has excellent bonding ability, which can ensure stable structural integrity during long-term service and is suitable for bonding different substrates such as metals and circuit boards.
[0072] 4.Excellent anti-aging stability After the heat aging test (85°C, 85%RH, 1000 hours), the square resistance only increased to 0.006 Ωm 2 , indicating that the material can still maintain stable conductive properties under high temperature and high humidity environments, and is suitable for electronic packaging and conductive bonding applications in harsh environments.
[0073] In summary, the tests show that this high-durability silicone conductive adhesive has excellent performance in conductivity, high temperature resistance, adhesion ability and aging stability, and has broad application prospects, especially suitable for electronic packaging, aerospace, automotive electronics and industrial applications with high temperature, high humidity and high reliability requirements.
[0074] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A highly durable silicone conductive adhesive, characterized in that: It includes the following specific components: organic silicon matrix, conductive filler, curing system, anti-aging additive, and tackifier; The mass fractions of each component are as follows: 50-100 parts of silicone matrix; Conductive filler 40-80 parts; Curing system 2-10 parts; 1-5 parts of anti-aging additive; 2-8 parts of tackifier; The high-durability silicone conductive adhesive also includes additives, which include a mesophase orientation agent, a self-repairing synergistic system, a nanophase interface reinforcing agent, and a nanobarrier layer; The mass fractions of each component of the additive are as follows: 2-6 parts of mesophase orientation agent; 3-8 copies of the self-repairing collaborative system; 4-10 parts of nanophase interface strengthener; Nano barrier layer 2-7 parts.
2. A highly durable organic silicone conductive adhesive according to claim 1, characterized in that: The organosilicon matrix is any one or more of polysiloxane or modified silicone resin; the conductive filler is any one or more of silver-plated copper powder, graphene or carbon nanotubes; the curing system is any one or more of peroxide curing agent, platinum catalyzed addition curing agent or moisture curing agent; the anti-aging additive includes any one or more of antioxidant, ultraviolet absorber and thermal stabilizer; the tackifier is any one or more of silane coupling agent or modified epoxy resin.
3. The highly durable organic silicone conductive adhesive according to claim 1, characterized in that: The mesophase orientation agent includes a block copolymer and a surface functionalized liquid crystal polymer; The block copolymer is any one or more of polyethylene oxide-polydimethylsiloxane-polyethylene oxide, polystyrene-polydimethylsiloxane-polystyrene or segmented polyurethane, and the molecular weight distribution of the block copolymer is between 10,000 and 100,000; The main chain structure of the surface functionalized liquid crystal polymer is any one or more of polystyrene, polymethyl methacrylate or polyamide, and the side chain contains any one or more of cyano, carboxyl, sulfonic acid or phosphoric acid functional groups.
4. The highly durable organic silicone conductive adhesive according to claim 1, characterized in that: The self-healing synergistic system includes nitrogen-doped graphene and aromatic heterocyclic functionalized silane; The nitrogen content in the nitrogen-doped graphene is 1-10 wt %, and the nitrogen exists in the form of pyridinic nitrogen, graphitic nitrogen or amine nitrogen; The aromatic heterocyclic functional silane contains any one or more of an imidazole ring, a thiophene ring, a benzothiazole ring or a benzimidazole ring structure.
5. The highly durable organic silicone conductive adhesive according to claim 1, characterized in that: The nanophase interface reinforcing agent is composed of triblock nanocarbon fibers and a supramolecular network reinforcing agent; The triblock carbon nanofiber has a carbon nanofiber as the main chain and functionalized polydimethylsiloxane grafted at both ends. The diameter of the triblock carbon nanofiber is 20-200 nm and the length is 1-10 μm. The supramolecular network enhancer consists of surface-modified Janus particles, one side of the surface of the Janus particles is modified with a hydrophobic group, and the other side of the surface of the Janus particles is modified with a hydrophilic group.
6. The highly durable organic silicone conductive adhesive according to claim 1, characterized in that: The nano barrier layer is composed of a nano metal-oxide heterostructure and a conductive polymer coating; The thickness of the oxide layer on the surface of the nano-metal-oxide heterostructure is 2-20 nm; The thickness of the conductive polymer coating is 5-50 nm.
7. The highly durable organic silicone conductive adhesive according to claim 6, characterized in that: The nanometal in the nanometal-oxide heterostructure is any one or more of silver nanoparticles, copper nanoparticles or nickel nanoparticles; the oxide layer is any one or more of tin oxide, zinc oxide and aluminum oxide; The conductive polymer coating is any one or more of polypyrrole, polyaniline or polythiophene.
8. A method for preparing the highly durable organic silicone conductive adhesive according to any one of claims 1 to 7, characterized in that: The specific steps include: S1, preparing an organic silicon matrix as a basic carrier of the conductive adhesive; S2, dispersing the conductive filler to form a stable dispersed state in the organic silicon matrix; S3, adding a curing system, the curing system is used to cross-link the silicone matrix; S4. Introduce anti-aging additives to improve the UV resistance, heat resistance and moisture resistance of the conductive adhesive; S5, adding a tackifier to enhance the interface bonding strength; S6, adding a mesophase orientation agent to optimize the conductive path of the conductive adhesive; S7, introduce a self-healing collaborative system and ensure its uniform dispersion; S8. Finally, add the nano-phase interface reinforcing agent and the nano-barrier layer, and after aging, form a stable and highly durable silicone conductive adhesive.
9. The method for preparing a highly durable organic silicone conductive adhesive according to claim 8, characterized in that: In the step S7, when the self-repairing synergistic system is added, the mixture is stirred and mixed at a speed of 500-1000 rpm for 60 minutes to ensure that it is evenly dispersed; Through subsequent low-temperature treatment at 40-60°C, the self-healing synergistic system forms a dynamic network, improving the fatigue resistance and self-healing properties of the conductive adhesive.
10. The method for preparing a highly durable organic silicone conductive adhesive according to claim 8, characterized in that: In the step S8, the nanophase interface strengthener is first added, and shearing stirring is performed at a speed of 3000-4000 rpm for 30 minutes to make it evenly distributed; Then, the nano-barrier layer was added under stirring conditions and continued to be stirred for 30 minutes to optimize its bonding with the silicone matrix; Finally, the conductive adhesive system is cured at a temperature of 25-40° C. for 12-24 hours to form a highly durable silicone conductive adhesive.
Citation Information
Patent Citations
High-temperature resistant low-dilatation coefficient heat conduction potting adhesive as well as preparation method and application thereof
CN107513368A
Organosilicon system conductive adhesive and preparation method thereof
CN111548765A
Room-temperature-curing high-strength high-thermal-conductivity and high-electric-conductivity silver adhesive
CN119490815A
Low-change-rate slurry as well as preparation and application thereof
CN119786121A
Conductive silicone resin composition and method of manufacturing same
KR102285124B1
Cited By
Self-repairing organic silicon conductive adhesive and preparation method thereof
CN120555010A
Ultraviolet curing organic silicon conductive adhesive and preparation method thereof
CN120623971A